Gerakan Front Nahdliyin Untuk Kedaulatan Sumber Daya Alam (FNKSDA): Melawan Ekstraksi Emas di Banyuwangi dengan Semangat Islam Progresif - Abdalla, Aufa Ulil Abshar (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The escalation of ecological crises is increasingly evident in contemporary society, particularly with the surge in ecological disasters across various regions of Indonesia. This phenomenon is intricately linked to the intensifying extreme weather patterns, a consequence of post-World War II industrialization and the unchecked expansion of industries in developing nations. This study delves into the ideologies and actions of the Front Nahdliyin for the Sovereignty of Natural Resources (FNKSDA) aimed at mitigating the unfolding ecological catastrophes, which are symptomatic of the ongoing crisis. It investigates how FNKSDA's initiatives intersect with the principles of progressive Islam. Notably, one of FNKSDA's key endeavors involves countering neo-extractivist practices spearheaded by PT BSI in Banyuwangi, which resulted in devastating mud floods in 2016. Employing a comprehensive literature review methodology encompassing scholarly works, journals, and pertinent press releases, this research unveils FNKSDA's alignment with progressive Islamic tenets. Conceptually, this alignment manifests through their interpretative approaches to religious texts, while in practice, it is evidenced through their advocacy for marginalized communities and steadfast resistance against oppressive systems.